Shattered dreams: the effects of changing the pension system late in the game - Andries de Grip; Maarten Lindeboom; Raymond Montizaan (Institute for the Study of Labor (IZA), 2009)
This paper assesses the impact of a dramatic reform of the Dutch pension system on mental health, savings behavior and retirement expectations of workers nearing retirement age. The reform means that public sector workers born on January 1, 1950 or later face a substantial reduction in their pension rights while workers born before this threshold date may still retire under the old, more generous rules. We employ a unique matched survey and administrative data set comprising male public sector workers born in 1949 and 1950 and find strong ex ante effects on mental health for workers who are affected by the reform. This effect increases as birth dates approach the threshold date. Furthermore, the effects differ in accordance with worker characteristics. Finally, we find that the response of those affected by the reform is to work longer and to save more.
urn:nbn:de:101:1-20090306272
Keywords: I12; J08; J14; J26; 330; Mental health; retirement; pension reform; causal effect; Rentenreform; Ruhegehalt; Wirkungsanalyse; Psychische Störung; Beamte; Niederlande